Localization of RNAi Machinery to Axonal Branch Points and Growth Cones Is Facilitated by Mitochondria and Is Disrupted in ALS - Gershoni-Emek, Noga; Altman, Topaz; Ionescu, Ariel; Costa, Christopher J.; Gradus-Pery, Tal; Willis, Dianna E.; Perlson, Eran (Frontiers in Molecular Neuroscience, 2018)
Local protein synthesis in neuronal axons plays an important role in essential spatiotemporal signaling processes; however, the molecular basis for the post-transcriptional regulation controlling this process in axons is still not fully understood. Here we studied the axonal mechanisms underlying the transport and localization of microRNA (miRNA) and the RNAi machinery along the axon. We first identified miRNAs, Dicer, and Argonaute-2 (Ago2) in motor neuron (MN) axons. We then studied the localization of RNAi machinery and demonstrated that mitochondria associate with miR-124 and RNAi proteins in axons. Importantly, this co-localization occurs primarily at axonal branch points and growth cones. Moreover, using live cell imaging of a functional Cy3-tagged miR-124, we revealed that this miRNA is actively transported with acidic compartments in axons, and associates with stalled mitochondria at growth cones and axonal branch points. Finally, we observed enhanced retrograde transport of miR-124-Cy3, and a reduction in its localization to static mitochondria in MNs expressing the ALS causative gene hSOD1G93A. Taken together, our data suggest that mitochondria participate in the axonal localization and transport of RNAi machinery, and further imply that alterations in this mechanism may be associated with neurodegeneration in ALS.